A blurry view of fuzzy objects: on the roles of low-resolution structural techniques in discovery and early characterization of intrinsically disordered proteins - Uversky, Vladimir N. (Frontiers in Biophysics, 2025)
The discovery of intrinsically disordered proteins (IDPs) (and, therefore, the establishment of the field of protein intrinsic disorder) was initially driven by low-resolution techniques, which overturned the established “lock-and-key” paradigm of structural biology by showing that some proteins exist as a dynamic conformational ensemble rather than a single fixed structure. Though unable to provide atomic-level detail offered by X-ray crystallography or NMR, these methods were the first to reveal that many functional proteins exist as a dynamic ensemble of conformations rather than a single fixed structure. Furthermore, these techniques highlighted a limitation of high-resolution methods such as X-ray crystallography, which often could not resolve disordered regions. Curiously, despite the fact that X-ray crystallography requires rigid, crystalized samples and portrays the proteins as aperiodic crystals, this technique provided some early hints of intrinsic disorder that came from the “missing residues” in X-ray structures. Ultimately, by identifying proteins that lacked stable structures, these initial experiments utilizing low-resolution techniques drove the development of advanced approaches, such as specialized NMR techniques, to better characterize the dynamics of these proteins. The goal of this review is to emphasize the roles of low-resolution structural techniques in establishing the IDP field by showing some illustrative examples of IDPs they helped to discover in the years preceding the formal acceptance of the protein intrinsic disorder concept.